(untitled) (Research, Society and Development, 2022)
The present article seeks to rescue the economic history of sisal from a technological point of view. The article aims to analyze the evolutionary process of technology in the sisal economy of Northeastern Brazil in order to describe the changes in the different defibration machines used in the defibration of sisal fiber. For the execution, the exploratory-descriptive and historical institutional research method was adopted, with a qualitative character, seeking to investigate, describe, and interpret the phenomena that occurred in the past. The results suggest that the evolutionary process of technology in sisal culture has not reached all regions of the Northeast, resists the unfolding of local realities and promotes a source of income for many rural workers.